Brown and Black Carbon Emitted by a Marine Engine Operated on Heavy Fuel Oil and Distillate Fuels: Optical Properties, Size Distributions, and Emission Factors. Issue 11 (15th June 2018) - Corbin, J. C.; Pieber, S. M.; Czech, H.; Zanatta, M.; Jakobi, G.; Massabò, D.; Orasche, J.; El Haddad, I.; Mensah, A. A.; Stengel, B.; Drinovec, L.; Mocnik, G.; et al.
Abstract: We characterized the chemical composition and optical properties of particulate matter (PM) emitted by a marine diesel engine operated on heavy fuel oil (HFO), marine gas oil (MGO), and diesel fuel (DF). For all three fuels, ∼80% of submicron PM was organic (and sulfate, for HFO at higher engine loads). Emission factors varied only slightly with engine load. Refractory black carbon (rBC) particles were not thickly coated for any fuel; rBC was therefore externally mixed from organic and sulfate PM. For MGO and DF PM, rBC particles were lognormally distributed in size (mode at d rBC ≈120 nm). For HFO, much larger rBC particles were present. Combining the rBC mass concentrations with in situ absorption measurements yielded an rBC mass absorption coefficient MACBC, 780nm of 7.8 ± 1.8 m 2 /g at 780 nm for all three fuels. Using positive deviations of the absorption Ångström exponent (AAE) from unity to define brown carbon (brC), we found that brC absorption was negligible for MGO or DF PM (AAE(370, 880 nm)≈1.0 ± 0.1) but typically 50% of total 370‐nm absorption for HFO PM. Even at 590 nm, ∼20 of the total absorption was due to brC. Using absorption at 880 nm as a reference for BC absorption and normalizing to organic PM mass, we obtained a MACOM, 370nm of 0.4 m 2 /g at typical operating conditions. Furthermore, we calculated an imaginary refractive index of (0.045 ± 0.025)( λ /370nm) −3 for HFO PM at 370 nm> λ > 660 nm, more than twofold greater than previous recommendations. Climate models should account for this substantial brC absorption in HFO PM. Plain Language Summary: We characterized the fundamental properties of marine engine exhaust that are relevant to its aerosol‐radiation interactions in climate models. In particular, we focussed on "brown carbon" light absorption (i.e., absorption in excess of that expected for the black carbon in canonical soot). We found that brown carbon can increase the direct radiative forcing of heavy‐fuel‐oil ship exhaust by 18% over snow. Key Points: Even at 590‐nm wavelength, brC in the exhaust of an engine operated on heavy fuel oil (HFO) was responsible for 20% of total PM absorption HFO contains very large rBC particles (mode at 640‐nm volume‐equivalent diameter) We report wavelength‐dependent imaginary refractive indices and mass absorption cross sections for brown carbon